Promotion or Suppression of Murine Intestinal Polyp Development by iNKT Cell Directed Immunotherapy - Wang, Ying; Sedimbi, Saikiran K.; Löfbom, Linda; Besra, Gurdyal S.; Porcelli, Steven A.; Cardell, Susanna L. (Frontiers in Immunology, 2019)
The glycosphingolipid α-galactosylceramide (α-GalCer) is a well described immune activator with strong anti-tumor properties in animal models. It is presented on CD1d and acts by stimulating the invariant, type I, natural killer T (iNKT) lymphocytes to rapidly secrete TH1 and TH2 associated cytokines. This in turn promotes activation of a diversity of immune cells including natural killer (NK) cells with anti-tumor functions. Prior to tumor development, iNKT cells can also perform tumor surveillance and naturally protect from emergence of cancer. In contrast, we have recently demonstrated that iNKT cells naturally promote polyps in the spontaneous murine adenomatous polyposis coli (Apc) ApcMin/+ model for colon cancer, associated with suppressed TH1 immunity and enhanced immunoregulation. Here we investigated whether iNKT cell directed immunotherapy could subvert the polyp promoting function of iNKT cells and reduce polyp growth in this model. We treated ApcMin/+ mice with α-GalCer, or synthetic derivatives of this ligand (C-glycoside and C20:2) that have enhanced immunoregulatory properties. Treatment with iNKT cell ligands led to increased iNKT cell division, but reduced iNKT cell frequencies, lower NK1.1 expression and elevation of PD-1. ApcMin/+ mice that had been treated either long-term (5 – 15 weeks of age), or short-term (12 – 15 weeks of age) with α-GalCer demonstrated a significant decrease in polyp burden. Surprisingly, long-term treatment with the TH1 biasing ligand C-glycoside did not have significant effects on polyps, while long-term treatment with the TH2 biasing ligand C20:2 enhanced polyp growth. In stark contrast, short-term treatment with C20:2 led to reduction in polyp numbers and size. Reduced polyp burden after long-term treatment was associated with increased expression of genes indicating a pro-inflammatory polyp microenvironment. Polyp-reducing short-term treatment led to CD8 T cell activation specifically in polyps, and decreased tumor infiltrating and splenic macrophages, and a switch towards a pro-inflammatory phenotype. Thus, iNKT cell directed therapy could subvert the natural polyp enhancing function of iNKT cells, overcome immunosuppression and reduce polyps. However, different iNKT cell activating ligands had opposite effects, and the timing of treatment had a major influence on outcomes.